Persepsi Masyarakat Tentang Keberadaan Bank Syariah Indonesia Cabang Pembantu Stabat - Anjur Perkasa Alam, Asmawarna Sinaga, Fitra Alpa Syafira, Rio Ramadhan Putra (Pusdikra Publishing, 2019)
Perceptions of the Community Concerning the Existence of Bank Syariah Mandiri Branch Stabat, This study explains the stabat community's perception of the existence of Bank Syariah Mandiri in Stabat City. The perception in question is the perception arising from the knowledge and profession of the community and the share of Islamic banks. This research is a qualitative research. Sources of data used are primary data and secondary data. Methods of data collection by doing obsevation, documentation and interviews. Data analysis techniques using data reduction, data presentation and conclusion drawing. The result of the research by Bank Syariah Mandiri is a bank located on the cross road of Stabat city. Its location is very strategic and facilitate stabat society to find it. Good service is provided by employees of Bank Syariah Mandiri Stabat. Motivation of work provided by the head of branches is also very influential to improve the work ethic is good. Good leaders are people who are able to motivate their employees to work in the spirit and can finish the job in accordance with the target work. Public interest arose because of the good service provided by the employees of Bank Syariah Mandiri Stabat. Bank Syariah Mandiri has a very important role to promote the Economy in Indonesia. So the result of research of public perception about Bank Syariah Mandiri kebaradaan very good effect.